The role of bacterial genital infections in spontaneous preterm delivery: a case-control study - Ahmadi, Amjad; Khadem Erfan, Mohammad Bagher; Roshani, Daem; Derakhshan, Safoura; Ramazanzadeh, Rashid; Farhadifar, Fariba; Mohsenpour, Behzad; Shahgheibi, Sholeh; Zarei, Mozhdeh; Salimizand, Himen; Nikkhoo, Bahram (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Spontaneous preterm delivery is defined as the beginning of the birth process before the 37th week of pregnancy. The presence of microorganisms in the fetal membranes is accompanied by an increase in the production of prostaglandin, one of the important factors associated with the prevalence of preterm birth. The invasion of microorganisms leads to the production of protease, coagulase, and elastase, which directly stimulate the onset of childbirth. We investigated the role of genital infections in women with preterm birth.The present case-control study was conducted in the west of Iran on 100 women with spontaneous preterm delivery (following 24 weeks of gestation and before 36 weeks and 6 days) as the case group and 100 women with normal delivery as controls. A questionnaire was applied to collect the data. Polymerase chain reaction and pathological examination of the placenta were performed.The average age in women with normal delivery (30.92±5.10) in women with spontaneous preterm delivery (30.27±4.93). The prevalence of Chlamydia trachomatis, Neisseria gonorrhea, Listeria monocytogenes, and Mycoplasma genitalium infections was zero in both groups. The highest prevalence of Gardnerella vaginalis was 19 (19%) in the case group and Ureaplasma parvum 15 (15%) in the control group. Also, Placental inflammation was zero in controls and 7(7%) in the patient group. There was a significant relationship between Gardnerella vaginalis bacteria and spontaneous preterm delivery.The results of our study showed that except for Gardnerella vaginalis bacteria, there is no significant relationship between the above bacterial infections and spontaneous preterm birth. Moreover, despite the significant reduction in the prevalence of many sexually transmitted infections in this research, it is still suggested to increase the awareness of people, including pregnant women, about the ways it can be transmitted by gynecologists and health and treatment centers.